Optimalisasi Pembinaan Keagamaan Anak melalui Integrasi Pembelajaran Al-Qur’an dan Ibadah Dasar: Optimizing Children’s Religious Development Through the Integration of Qur’anic Learning and Basic Worship - Jamil, Ahmad; Zahra , Raudhatuz; Akmalia, Syalfadhila; Kamilah , Nasiroh Wardatul (Khadimul Mujtama’: Journal of Community Service, 2026)
Religious education for children plays an important role in developing religious character from an early age. However, many Qur’anic learning centers still face limitations in integrating Qur’anic instruction with basic worship practices, which affects the effectiveness of religious development programs. This community service activity was conducted at TPQ Al-Ikhwaniyah in Rancalabuh Village, Kemiri District, Tangerang Regency, involving 47 students aged 4–18 years over a period of three weeks. The program aimed to improve religious education through the integration of Qur’anic reading instruction, basic worship practices, character education, and Islamic learning assistance. The implementation methods included preliminary observation, learning assistance, worship practice sessions, moral education, and evaluation through participatory observation and interviews with TPQ administrators. The results indicated increased student participation, improved Qur’anic reading skills, better understanding of ablution and prayer procedures, and enhanced learning motivation among participants. In addition, the provision of Qur’anic learning facilities contributed to a more conducive learning environment. The findings suggest that integrating Qur’anic learning with basic worship practices is an effective approach to strengthening children’s religious development in rural communities.